A cross-sectional vaccination coverage study in preschool children attending nurseries-kindergartens: Implications on economic crisis effect. Issue 1 (2nd January 2017) - Georgakopoulou, Theano; Menegas, Damianos; Katsioulis, Antonis; Theodoridou, Maria; Kremastinou, Jenny; Hadjichristodoulou, Christos
ABSTRACT: Vaccination coverage studies are important in determining a population's vaccination status and strategically adjusting national immunization programs. This study assessed full and timely vaccination coverage of preschool children aged 2–3 y attending nurseries-kindergartens (N-K) nationwide at the socioeconomic crisis onset. Geographically stratified cluster sampling was implemented considering prefectures as strata and N-K as clusters. The N-K were selected by simple random sampling from the sampling frame while their number was proportional to the stratum size. In total, 185 N-K (response rate 93.9%) and 2539 children (response rate 81.5%) participated. Coverage with traditional vaccines for diphtheria-tetanus-pertussis, polio and measles-mumps-rubella was very high (>95%), followed by Haemophilus influenzae type b and varicella vaccines. Despite very high final coverage, delayed vaccination was observed for hepatitis B (48.3% completed by 12 months). Significant delay was observed for the booster dose of pneumococcal conjugate vaccines (PCV) and meningococcal C conjugate vaccines (MCC). Of the total population studied, 82.3% received 3 PCV doses by 12 months, while 62.3% received the fourth dose by 24 months and 76.2% by 30 months. However, 89.6% received at least one MCC dose over 12 months. Timely vaccinated for hepatitis A with 2 doses by 24 months were 6.1%. Coverage was significantly low for Rotavirus (<20%) and influenza (23.1% one dose). High vaccination coverage is maintained for most vaccines at the beginning of the crisis in Greece. Coverage and timeliness show an increasing trend compared to previous studies. Sustained efforts are needed to support the preventive medicine system as socioeconomic instability continues.